Tissue-Dependent Tumor Microenvironments and Their Impact on Immunotherapy Responses - Oliver, Amanda J.; Lau, Peter K. H.; Unsworth, Ashleigh S.; Loi, Sherene; Darcy, Phillip K.; Kershaw, Michael H.; Slaney, Clare Y. (Frontiers in Immunology, 2018)
Recent advances in cancer immunology have led to a better understanding of the role of the tumor microenvironment (TME) in tumor initiation, progression, and metastasis. Tumors can occur at many locations within the body and coevolution between malignant tumor cells and non-malignant cells sculpts the TME at these sites. It has become increasingly clear that there are specific differences of the TMEs at different anatomical locations, and these tissue-specific TMEs regulate tumor growth, determine metastatic progression, and impact on the outcome of therapy responses. Herein, we review the scientific advances in understanding tissue-specific TMEs, discuss their impact on immunotherapeutic response, and assess the current clinical knowledge in this emerging field. A deeper understanding of the tissue-specific TME will help to develop effective immunotherapies against tumors and their metastases and assist in predicting clinical outcomes.